Lingkungan pembelajaran daring, Hubungan Lingkungan Pembelajaran Daring dengan Kejenuhan Belajar Mahasiswa Pendidikan IPS - Purnama Sari, Rita; Alfia Purwandari, Dian; Saipiatuddin, Saipiatuddin (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
This study aims to determine correlation online learning environment with study burnout of Social Studies Education students, Faculty of Social Sciences, State University of Jakarta. The method in this study uses a quantitative approach. The sampling technique used is simple random sampling. The population used in this study was the Social Studies Education students of the 2019-2021 class as many as 254 students and the total sample was 155 respondents. Based on the analysis of the product moment value of sig. (2-tailed) 0.000 is less than 0.05 and Rcount (-0.416). The results of this study can be concluded that there is a negative correlation the online learning environment with student study burnout of Social Studies Education. The result reflect contrary of online learning environment to get down study burnout so it had the online learning environment better.